Holt-Oram Syndrome: A Variety of Heart-Hand Syndrome - Ahmed, Md Khurshed; Hoque, Harisul; Zaman, SM Mustafa; Rahman, Mukhlesur; Khaled, Md Fakhrul Islam; Chowdhury, MSI Tipu; Bashar, Adnan; Sultan, Md Ashraf Uddin; Fatema, Nilufar (University Heart Journal, 2018)
Holt-Oram syndrome (HOS) is a heart-upper limb malformation complex , is a rare autosomal dominant disorder, caused by a mutation in the TBX5 gene located on chromosome 12 and near complete penetrance but variable expression. Holt and Oram first described this syndrome in 1960. Approximately 40% of cases represent new mutations. The syndrome is associated with defective development of cardiac structures that results in atrial septal defect(ASD), most commonly the secundum type; heart block of varying degree or both.The syndrome is characterized by cardiac malformations and aplasia or hypoplasia of the thumb. The incidence of HOS is estimated at 1:100,000 live births. In the literature, it is also known as atriodigital syndrome, heart-hand syndrome, upper limb-cardiovascular syndrome, cardiac-limb syndrome, or cardiomelic syndrome. Herein, we report a 45-year-old female case of HOS presenting a large ostium secundum type ASD along with congenitally fusion of carpal bones in both hands and absence of right first metacarpal bone with triphalagial thumb where as hypoplastic proximal phalange. In left hand, hypoplastic first metacarpal bone and hypoplastic thumb with syndactyly of both thumb with index finger. University Heart Journal Vol. 13, No. 2, July 2017; 67-71